An X-ray view of the ambiguous nuclear transient AT2019pev. Issue 4 (26th July 2022) - Yu, Zhefu; Kochanek, C S; Mathur, S; Auchettl, K; Grupe, D; Holoien, T W-S
ABSTRACT: AT2019pev is a nuclear transient in a narrow-line Seyfert 1 galaxy at z = 0.096. The archival ultraviolet, optical, and infrared data showed features of both tidal disruption events and active galactic nuclei (AGNs), and its nature is not fully understood. We present detailed X-ray observations of AT2019pev taken with Swift, Chandra, and NICER over 173 d of its evolution since the first Swift XRT epoch. The X-ray luminosity increases by a factor of 5 in 5 d from the first Swift XRT epoch to the light-curve peak. The light curve decays by a factor of 10 over ∼75 d and then flattens with a weak re-brightening trend at late times. The X-ray spectra show a 'harder-when-brighter' trend before peak and a 'harder-when-fainter' trend after peak, which may indicate a transition of accretion states. The archival ground-based optical observations show similar time evolution as the X-ray light curves. Beyond the seasonal limit of the ground-based observations, the Gaia light curve is rising towards an equally bright or brighter peak 223 d after the optical discovery. Combining our X-ray analysis and archival multiwavelength data, AT2019pev more closely resembles an AGN transient.